Risk of cancer in patients with genital warts: A nationwide, population-based cohort study in Taiwan - Cho, Ching-Yi; Lo, Yu-Cheng; Hung, Miao-Chiu; Lai, Chou-Cheng; Chen, Chun-Jen; Wu, Keh-Gong (PloS one, 2017)
Condyloma acuminata currently affects around 1% of sexually active adults, and its incidence is increasing. The coexistence of genital warts (GW) and certain cancers and an association between human papillomavirus (HPV) and various malignancies have been reported. Therefore, we conducted this large national study to analyze the risk of malignancies among men and women with GW in Taiwan. Between January 2000 and December 2013, approximately 3 million patients were reported to the National Health Insurance Research Database of Taiwan. Of these patients, 21,763 were diagnosed with GW. In the same time period, a total of 213,541 cancer cases were reported to the registry, of which 1002 were recorded among patients with GW. The age-specific incidence rates of GW and standardized incidence ratios (SIRs) of malignancies compared to the general population were calculated. Women acquired GW earlier than men, with a mean age at diagnosis of 32.63±12.78 years. The highest incidence rate for both genders peaked at 20-29 years. Of the 1002 patients with GW and malignancies, the SIR was 1.95 (95%CI 1.83-2.07). The most markedly increased risk was found for HPV-related cancers, with a SIR of 9.74 (95%CI 3.70-15.77). Significantly elevated risks were also noted for smoking-related cancers, anogenital cancers, cervix in situ, colon, rectum, lung, kidney, and prostate cancers. Most cancers developed within 10 years after the diagnosis of GW. Patients with GW have an increased risk of HPV-related cancers, especially anogenital malignancies in Taiwan. The elevated risk of other cancers highlights differences in exposure and risk factors among patients with GW compared to the general population. Cancer screening and HPV vaccination programs should be emphasized for at-risk patients.